The sorrow comes when I’m having moments of joy—experiences of parenting a live baby following a previous stillbirth: an interpretative phenomenological analysis - Blocksidge, Hope; Heazell, Alexander E. P.; Wittkowski, Anja; Smith, Debbie M. (Frontiers in Psychology, 2024)
Stillbirth can lead to complex and varied psychological outcomes for parents. Many choose to have another pregnancy following a stillbirth; however, little is known about the experience of parenting and bonding with the subsequent baby. Couples, who were the biological parents of a stillborn baby and at least one subsequent live baby aged under five, were recruited and interviewed individually. Data were analysed using interpretative phrenomenological analysis. Twelve individual interviews (of six couples) were conducted and four themes with nine subthemes were developed. Theme 1 “Back to the starting line: pregnancy as a means to an end” captured parents’ desire to bring a live baby home with pregnancy being experienced alongside fear, trauma, and grief. Theme 2 “Reality hits” encapsulated the experience of arriving home and feeling overwhelmed by the demands of a new-born baby. Theme 3 “Being a living and loss parent” captured the experience of being a parent to both a living and non-living baby with conflicting emotions. Theme 4 “Protection: ‘I need him there next to me, so I know he’s alive’” represented the fear some parents felt when parenting their live baby and included parents’ strategies to manage this anxiety. This study presents novel insight into the complexities of being a parent to a stillborn baby in tandem with a live baby, with difficulties arising in bonding, and managing emotional distress linked to trauma and grief. Potential implications for care includes a need for increased training for professionals providing postnatal care.